La economía china en la coyuntura económica mundial y las implicancias para el Perú - Aquino Rodríguez, Carlos (2011)
China has been growing at high rates in the last years and it is becoming the engine of the world economy. In the 2009 world economic crisis the Chinese government took several economic policies that allowed it to avoid been affected. Given the uncertainties surrounding the world economy in the year 2012 it is expected that China will also grow fast and sustain the world economy. By doing this it will help the Peruvian economy given the fact that China has become already our top trading partner.